Coordination of heterogeneous nonlinear multi-agent systems with prescribed behaviours. Issue 10 (3rd October 2017) - Tang, Yutao
ABSTRACT: In this paper, we consider a coordination problem for a class of heterogeneous nonlinear multi-agent systems with a prescribed input–output behaviour which was represented by another input-driven system. In contrast to most existing multi-agent coordination results with an autonomous (virtual) leader, this formulation takes possible control inputs of the leader into consideration. First, the coordination was achieved by utilising a group of distributed observers based on conventional assumptions of model matching problem. Then, a fully distributed adaptive extension was proposed without using the input of this input–output behaviour. An example was given to verify their effectiveness.